The meanings of Parkinson's disease for the elderly, families and the community - Faria, Amélia Aparecida Alarcon (2024)
Introduction: In a context of sociodemographic and epidemiological changes at a global level, it is possible to notice a notable increase in population aging, which is directly associated with a significant increase in chronic diseases. Objective: To successfully develop methods that allow management, treatment and possible rehabilitation of patients with PD, thus helping to formulate plans aimed at reducing the harmful impact of this pathology on patients' lives. Methodology: Integrative research. 11 articles were selected with the descriptors used in accordance with the inclusion and exclusion criteria, which were presented in the summary table. Results: It was observed that the most studied years are concentrated between 2020 and 2024. The most researched objectives were developed on the survey of scientific works that point out updates in Parkinson's disease, as well as aging, demographic aspects, transition of family members from elderly people with Parkinson's disease, Diagnosis of Parkinson's disease and Nursing care for people with Parkinson's disease in Primary and Multidisciplinary Health Care. Thematic categories were identified and included according to the articles researched, “Aging”, “Demographic aspects”, “Parkinson’s Diseases”, “Diagnosis”, “Nursing Care for the elderly with Parkinson’s Diseases” and “Primary Health Care and Multidisciplinary treatment for elderly people with Parkinson’s disease.” Conclusion: Interventions are necessary to identify the specific concerns of family members, strengthening and facilitating the transition process to the role of caregiver in the face of changes in routine caused by Parkinson's disease. The importance of nurses within the multidisciplinary team is highlighted. However, the effectiveness of nurses' intervention in the treatment of Parkinson's patients is mentioned briefly and discreetly. Therefore, it is essential that the nurse is present from the beginning of the patient's condition, helping them even when more advanced complications of the disease arise.